Curve-Skeleton Properties, Applications, and Algorithms - Cornea, Nicu D.; Silver, Deborah; Min, Patrick (IEEE transactions on visualization and computer graphics, 2007)
Curve-skeletons are thinned 1D representations of 3D objects useful for many visualization tasks including virtual navigation, reduced-model formulation, visualization improvement, animation, etc. There are many algorithms in the literature describing extraction methodologies for different applications; however, it is unclear how general and robust they are. In this paper, we provide an overview of many curve-skeleton applications and compile a set of desired properties of such representations. We also give a taxonomy of methods and analyze the advantages and drawbacks of each class of algorithms.